BIG AND SMALL FISH IN THE SEA OF PATENT LITIGATION: AN ANALYSIS OF THE AMP v. USPTO DECISION AND ITS EFFECT ON LARGE AND SMALL BUSINESSES - Hershey, Kevin (Journal of Law and Commerce, 2013)
BIG AND SMALL FISH IN THE SEA OF PATENT LITIGATION: AN ANALYSIS OF THE AMP v. USPTO DECISION AND ITS EFFECT ON LARGE AND SMALL BUSINESSES